재가 양육미혼모가 지각한 자아존중감, 사회적지지, 상태불안 간의 관계 - 김혜순(Hye-Soon Kim); 이명희(Myung-Hee Lee) (한국콘텐츠학회 논문지, 12(11), 2012)
The purpose of this study was to investigate the degrees of and relationships between self-esteem, social support, and state anxiety in community-dwelling unmarried mother raising a child. Descriptive correlational study design was used. Data were collected from 65 participants with self-report questionnaires from May to December, 2011. First, the mean of self-esteem was 3.52, social support 3.49, and state anxiety 2.47 respectively. Second, the correlation between self-esteem and social support was also statistically significant(r=.286, p=.021), the correlation between self-esteem and state anxiety was statistically significant(r=-.780, p=<.001), and the correlation between social support and state anxiety was also statistically significant(r=-.425, p=<.001). Self-esteem for unmarried mother raising a child in the study was confirmed as the primary important concept. Also, the correlation between social support and state anxiety was verified as significant. Therefore, study is needed to develop a nursing intervention program for self-esteem and social support improvement, and state anxiety decrease of unmarried mother raising a child. 본 연구의 목적은 재가 양육미혼모 65명을 대상으로 재가 양육미혼모가 지각한 자아존중감, 사회적지지 및 상태불안 정도와 상관관계를 파악하여 재가 양육미혼모의 간호중재를 위한 기초 자료를 제공하기 위하여 실시하였다. 본 연구결과 재가 양육미혼모가 지각한 자아존중감 3.52점, 사회적지지 3.49점, 상태불안 2.47점으로 중간수준 이상의 점수를 나타내었다. 자아존중감은 연령, 아버지의 교육정도에 따라 통계적으로 유의한 차이가 나타났고, 사회적지지는 연령, 평소피로감에 따라 통계적으로 유의한 차이가 나타났으며, 상태불안은 연령, 평소 피로감에 따라 통계적으로 유의한 차이가 나타났다. 재가 양육미혼모가 지각한 자아존중감과 사회적지지(r=.286, p=.021)는 유의한 정적 상관관계를, 자아존중감과 상태불안(r=-.780, p=<.001) 그리고 사회적지지와 상태불안(r=-.425, p=<.001)은 유의한 부적 상관관계가 나타났다. 이상의 연구결과를 바탕으로 자아존중감에 대한 영향 변수로서 상태불안과 사회적지지와의 관련성을 확인함으로써 재가 양육미혼모의 자아존중감과 사회적지지를 향상시키고 상태불안을 감소시킬 수 있는 간호중재 프로그램 개발 시기초자료로 활용되기를 기대한다.